A next-generation optical sensor for IceCube-Gen2 - Ishihara, Aya; Shimizu, Nobuhiro; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, Juan A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, Patrick; Alves, A. A.; Amin, N. M.; et al. (Proceedings of Science, 2022)
For the in-ice component of the next generation neutrino observatory at the South Pole, IceCubeGen2, a new sensor module is being developed, which is an evolution of the D-Egg and mDOM sensors developed for the IceCube Upgrade. The sensor design features up to 18 4-inch PMTs distributed homogeneously in a borosilicate glass pressure vessel. Challenges arise for the mechanical design from the tight constraints on the bore hole diameter (which will be 2 inches smaller than for IceCube Upgrade) and from the close packing of the PMTs. The electronics design must meet the space constraints posed by the mechanical design as well as the power consumption and cost considerations from over 10,000 optical modules being deployed. This contribution presents forward-looking solutions to these design considerations. Prototype modules will be installed and integrated in the IceCube Upgrade.
CRIS-Team Scopus Importer:2023-08-15